EXPERT SYSTEM FOR DIAGNOSIS OF STUNTING DISEASE IN TODDLERS USING CERTAINTY FACTOR METHOD AND WEB-BASED ANALYTICAL HIERARCHY PROCESS - Ramadan, Mahmud; Sentosa, Sabar; Minahjaya, Suhana (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2025)
Stunting in toddlers is a serious health problem that can affect children's physical and cognitive development. In Indonesia, stunting is one of the important indicators in assessing the quality of public health. However, early diagnosis and treatment of stunting are still challenges, especially in areas with limited access to adequate health services. To overcome this problem, the development of a web-based expert system is a potential solution. This system utilizes the Certainty Factor (CF) method to assess the level of certainty of diagnosis and the Analytical Hierarchy Process (AHP) to determine the weight of the criteria that influence the diagnosis. By combining these two methods, it is hoped that the expert system developed can provide a diagnosis of stunting in toddlers quickly, accurately, and consistently, and assist health workers in making the right decisions. This study aims to design and implement a